Estimated Glomerular Filtration Rate, Proteinuria, and Risk of Cardiovascular Diseases and All-cause Mortality in Diabetic Population: a Community-based Cohort Study. Issue 1 (December 2017) - Wang, Anxin; Chen, Guojuan; Cao, Yibin; Liu, Xiaoxue; Su, Zhaoping; Luo, Yanxia; Zhao, Zhan; Li, Xia; Chen, Shuohua; Wu, Shouling; Guo, Xiuhua
Abstract Data about associations between estimated glomerular filtration rate (eGFR) and proteinuria with cardiovascular diseases (CVDs) and all-cause mortality among diabetic population is less described. We aimed to describe these associations in Chinese diabetic population, and investigate the difference between sexes. The study was based on 8, 301 diabetic participants in the Kailuan study, who was free of CVDs at baseline. We used Cox proportional hazard models to examine the associations of eGFR and proteinuria with CVDs and all-cause mortality. A stratified analysis by gender was performed. During a median follow-up of 8.05 years, 917 deaths and 813 incident CVDs occurred. Adjusted for all potential confounders, eGFR was associated with all-cause mortality, but not associated with incidence of CVDs. Compared to those with eGFR ≥ 90 ml/min/1.73 m2, Participants with eGFR <45 ml/min/1.73 m2 had 1.50 fold higher risk of all-cause mortality. Adjusted for all potential confounders, proteinuria was associated with risk of both CVDs and all-cause mortality. Additionally, the risk of all-cause mortality by proteinuria was greater in women than that in men. Both lower eGFR and proteinuria are independent risk factors for all-cause mortality in the Chinese diabetic population. Proteinuria conferred excessive risk for CVDs, and especially in women.